2003
DOI: 10.1128/mcb.23.6.2151-2161.2003
|View full text |Cite
|
Sign up to set email alerts
|

The TRE17 Oncogene Encodes a Component of a Novel Effector Pathway for Rho GTPases Cdc42 and Rac1 and Stimulates Actin Remodeling

Abstract: The Rho family GTPases Cdc42 and Rac1 play fundamental roles in transformation and actin remodeling. Here, we demonstrate that the TRE17 oncogene encodes a component of a novel effector pathway for these GTPases. TRE17 coprecipitated specifically with the active forms of Cdc42 and Rac1 in vivo. Furthermore, the subcellular localization of TRE17 was dramatically regulated by these GTPases and mitogens. Under serumstarved conditions, TRE17 localized predominantly to filamentous structures within the cell. Epider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 55 publications
2
51
0
Order By: Relevance
“…As reported previously (Masuda-Robens et al, 2003;Martinu et al, 2004), TRE17 localized at the plasma membrane and tubular endosomes (Fig. 4).…”
Section: Compartmentalization Of Dubs Contributes To Recognition Of Csupporting
confidence: 54%
See 1 more Smart Citation
“…As reported previously (Masuda-Robens et al, 2003;Martinu et al, 2004), TRE17 localized at the plasma membrane and tubular endosomes (Fig. 4).…”
Section: Compartmentalization Of Dubs Contributes To Recognition Of Csupporting
confidence: 54%
“…Interestingly, TRE17 is known to bind Arf6, a key regulatory factor for the CIE trafficking pathway. It has been shown that Arf6 and TRE17 colocalize at the plasma membrane and tubular recycling endosomes (Masuda-Robens et al, 2003;Martinu et al, 2004). In addition, Rueckert and Haucke (Rueckert and Haucke, 2012) have shown that subcellular localization of TRE17 depends on Arf6.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence was performed as previously described, except that saponin (0.1%) was used in lieu of Triton X-100 (Masuda-Robens et al, 2003). Briefly, cells were fixed with formaldehyde, permeabilized, incubated with primary antibodies for 2-3 hours, then washed.…”
Section: Immunofluorescence Confocal Microscopymentioning
confidence: 99%
“…Anti-GST has been described previously (19). Anti-ubiquitin (Ub) antibody (FK2) was purchased from Affiniti Research Products, and antimaltose-binding protein (MBP) from New England Biolabs.…”
Section: Methodsmentioning
confidence: 99%
“…The entire open reading frame was subcloned into the mammalian expression vector pEBG to generate a GST-tagged fusion protein (CaM⅐pEBG). Hemagglutinin (HA)-TRE17(long), HA-TRE17(onco), and T17(447)/pcDNA3 have been described previously (18,19). Point mutants HA-T17(447)/ F328E/pcDNA3, T17(447)/L319D, W320D/pcDNA3, HA-T17(447)/ V306D,L311D)/pcDNA3, and HA-T17(447)/R15A/pcDNA3 were generated by overlap extension PCR.…”
Section: Methodsmentioning
confidence: 99%